Social work from assessment to intervention - Heslop, Philp; Meredith, Cathryn (SAGE Publications, Inc., 2018)
"This book equips readers with the essential knowledge and skills to undertake effective assessments and appropriate interventions with confidence. In part one the authors unpick exactly what assessment is, outline the assessment toolkit, apply this to practice and discuss the ins and outs of the development of a clear care plan. Drawing on activities, case studies and service user perspectives part two guides readers through the application of different intervention methods in varied contexts with diverse service user groups. This book focuses on key issues such as resilience, professional values and ethics, complexity and reflective practice, helping students not only get to grips with all the essential theory but also to develop to emotional and professional intelligence."--Page 4 de la couverture.